1996
DOI: 10.1007/bf01806499
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of MDM-2 in breast carcinomas

Abstract: MDM-2 is a cellular oncoprotein that binds to the p53 protein and abrogates its growth-suppressing function. At least seven MDM-2 mRNAs and five proteins (p90, p85, p76, p74, and p57) have been reported in tissue culture. MDM-2 gene amplification occurs in human sarcomas and high-grade gliomas. MDM-2 overexpression without gene amplification has been reported in leukemias and lymphomas. Here we report MDM-2 mRNA overexpression in 24 (73%) out of 33 cases of human breast carcinoma as compared with normal breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 26 publications
4
80
0
1
Order By: Relevance
“…Overexpression due to hitherto unknown reasons might play a role in some hematopoietic malignancies. MDM-2 has been documented to be highly expressed in 40% cases of AML (Faderl et al, ;Bueso-Ramos et al, 1993;Seliger et al, 1996). A small study of MDS found MDM-2 to be highly expressed in ®ve out of seven samples (Bueso-Ramos et al, 1993), a large study found normal levels of the protein in 21 cases of MDS .…”
Section: Ink4 Family Of Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression due to hitherto unknown reasons might play a role in some hematopoietic malignancies. MDM-2 has been documented to be highly expressed in 40% cases of AML (Faderl et al, ;Bueso-Ramos et al, 1993;Seliger et al, 1996). A small study of MDS found MDM-2 to be highly expressed in ®ve out of seven samples (Bueso-Ramos et al, 1993), a large study found normal levels of the protein in 21 cases of MDS .…”
Section: Ink4 Family Of Proteinsmentioning
confidence: 99%
“…MDM-2 has been documented to be highly expressed in 40% cases of AML (Faderl et al, ;Bueso-Ramos et al, 1993;Seliger et al, 1996). A small study of MDS found MDM-2 to be highly expressed in ®ve out of seven samples (Bueso-Ramos et al, 1993), a large study found normal levels of the protein in 21 cases of MDS . MDM-2 was reported to be frequently (450%) overexpressed in multiple myeloma (Lai et al, 1998) and high grade NHL (Finnegan et al, 1994;Moller et al, 1999) and moderately frequently in low grade NHL, CLL (Bueso-Ramos et al, 1993;Watanabe et al, 1994) and childhood ALL (Zhou et al, 1995;Marks et al, 1997;Gustafsson and Stal, 1998).…”
Section: Ink4 Family Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent data suggest that overproduction of HDM2 may result from mechanisms other than gene ampli®cation and include chromosomal translocations (Berberich and Cole, 1994), increased levels of hdm2 mRNA (Bueso-Ramos et al, 1993;Watanabe et al, 1994), or enhanced translation (Landers et al, 1994;Capoulade et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of the MDM2 protein confers oncogenic properties to NIH3T3 cells (Fakharzadeh et al, 1991), immortalizes rat embryonic ®broblasts and transforms them in cooperation with activated ras (Finlay, 1993). Approximately 5 ± 10% of all human tumours contain overexpressed MDM2, suggesting that it contributes to tumour development and/or tumour progression (Bueso-Ramos et al, 1993JuvenGershon and Oren, 1999;Oliner et al, 1992). MDM2 is believed to be oncogenic due to negative regulation of the p53 tumour suppressor gene product (JuvenGershon and Oren, 1999).…”
Section: Introductionmentioning
confidence: 99%